Hydrological Forecasting Technology and Its Application in Xizhijiang River Basin - XIE Hehai; LIANG Zhihong; ZHA Dawei; MA Xinghua (Renmin Zhujiang)
With the development of social economy, the problem of flood control caused by urbanization is more and more serious. Xizhijiang River Basin is the first-level tributary of Dongjiang River Basin, and the lower reaches is Huizhou flood control area. The flood evolution system of Xizhijiang River Basin is developed based on BS model. Taking the Andun River Basin, which is relatively less affected by human activities in the upper reaches of Xizhijiang River Basin as an example, this paper mainly studies the applicability of TOPMODEL and Xin'anjiang River model in hydrological forecasting of Xizhijiang River Basin. The simulation results of the hydrological forecasting from the TOPMODEL and Xin'anjiang River mode show that the accuracy of runoff simulation is high, and the parameter variation range is small. Therefore, the two models are suitable for this Basin, and the results lay the foundation for the simulation of TOPMODEL and Xin'anjiang River Model in the whole Xizhijiang River Basin.